Poetics, plays, and performances the politics of modern Indian theatre - Dalmia, Vasudha (Oxford University Press, 2008)
Addressing the political and aesthetic concerns of modern Indian theatre, propelled by the urban interest in folk theatre and the popularity of Brecht in connection with this, this work focuses on the political aspects, as portrayed in modern Indian theatre.